PENGARUH CUSTOMER VALUE TERHADAP MINAT MEREFERENSIKAN MELALUI BRAND IMAGE (Studi Empirik pada Mahasiswa Universitas YARSI)
This study aims to determine the effect of customer value on referring interest through brand images. In addition, this study is also to determine whether brand image mediates the effect of customer value and brand image on referring interest. The population of this research is students of various study programs at YARSI University. The research was conducted using a survey method by distributing questionnaires to 120 students from various study programs in YARSI University. The analytical tool used is path analysis. The results showed that customer value has a positive and significant effect on referring interest. The results also show that brand image  mediates the influence of customer value on the interest in referring students at YARSI University